An application of numerical methods to the prediction of strata methane flow in longwall mining - Ediz, I.G. (1991)
This research describes an application of numerical methods for the prediction of strata methane flow into mine workings around a longwall coal face employing methane drainage. This method of methane prediction was developed by solving the time-dependent gas flow equation using the finite element analysis. Having obtained the gas pressure distribution throughout the finite element mesh, a mass flow equation was derived to calculate methane flow rate for a given mining boundary. A computer program for the prediction of methane flow was then developed by devising appropriate modifications and additions to a finite element package originally written for heat flow by PAFEC limited. Stress analysis was also carried out in order to provide an understanding of stress fields around a longwall face to evaluate the induced permeabilities under these stress fields.